Cardiovascular magnetic resonance as an initial screening tool in individuals with SLE and chest pain - Samuelsson, Isak; Thalén, Simon; Grosso, Giorgia; Lundin, Magnus; Engblom, Henrik; Sörensson, Peder; Gunnarsson, Iva; Ugander, Martin; Svenungsson, Elisabet (Lupus Science and Medicine, 2025)
Objective Individuals with SLE commonly report chest pain or discomfort. We performed cardiovascular magnetic resonance (CMR) to differentiate coronary artery disease (CAD), coronary microvascular dysfunction (CMD), pericarditis and myocarditis in individuals with SLE who presented with chest symptoms. We also assessed the clinical utility of CMR. Methods Adults with SLE were included if reporting chest pain or dyspnoea suggestive of cardiac involvement to a rheumatologist between 2018 and 2023. Individuals underwent CMR, including quantitative myocardial perfusion mapping at rest and during adenosine stress if not contraindicated. CAD, CMD, pericarditis and myocarditis were identified by CMR. Confirmatory investigations were performed when indicated. We reviewed medical files to assess if CMR led to altered medical treatment or invasive interventions. Results Nineteen individuals with SLE (84% female) with a median age of 39 (IQR 31–55) years underwent CMR, of whom 14 (74%) were examined using adenosine stress. Symptoms prompting inclusion were pleuritic chest pain in 10/19 (53%), chest pain triggered by exercise or relieved by nitrates or rest in 2/19 (11%), other types of chest pain in 5/19 (26%) and dyspnoea suggestive of cardiac involvement in 2/19 (11%). CAD, CMD and pericarditis were diagnosed in 3/14 (21%), 2/14 (14%) and 3/19 (16%) individuals, respectively. None had myocarditis. CMR revealed no cause of chest symptoms in 12/19 (63%). The CMR results led to altered medical management in 6/19 (32%) individuals. Conclusions This cross-sectional study highlights cardiac ischaemia as a cause of chest symptoms in SLE. Notably, CAD and CMD were together more common than pericarditis and myocarditis. CMR may aid early detection and treatment of these conditions, as it altered medical management in one-third of cases. Larger studies are needed to confirm our findings and prospectively evaluate the long-term prognostic impact of early CMR in symptomatic individuals with SLE.
Publisher Copyright: © Author(s) (or their employer(s)) 2025. Re-use permitted under CC BY. Published by BMJ Group.
Keywords: Atherosclerosis; Cardiovascular Diseases; Lupus Erythematosus, Systemic; Magnetic Resonance Imaging; Microcirculation